The scarcity of domestic energy : a study in three villages. - Best, Marc (Department of Environmental and Geographical Science, 2015)
Very little information is available on domestic fuel consumption in African villages in Southern Africa. And yet, it is a problem that concerns a large number of people, and which is contributing to environmental deterioration. At three villages, in Lesotho, Transkei and KwaZulu, the collection and consumption of wood, dung and paraffin were recorded. The largest quantities of energy are consumed in KwaZulu with the least in the Transkei (only slightly below Lesotho). The total consumption of energy largely depends on the availability of wood. When wood becomes scarce, dung is burnt for heat and cooking. Paraffin is used for light, and for cooking by some women. Wood and dung are burnt at efficiencies of below 3%. The most obvious short term solution, to shortages of energy, is to raise the efficiency with which fuel is burnt. In the long term, alternative energy sources must be developed.